The effects of perfectionism in elite sport: Experiences of unhealthy perfectionists - Sellars, P. A.; Evans, L.; Thomas, O. (The Sport Psychologist, 2016)
This study examined the perfectionism experiences of 10 elite perfectionist athletes (5 male and 5 female). Following completion of the Sport Multidimensional Perfectionism Scale-2 (Gotwals & Dunn, 2009), a purposeful sample of unhealthy perfectionists were interviewed in relation to the study aims. Several themes emerged from the data that related to: effects of perfectionism and its antecedents on sporting experiences, specificity and level of perfectionism, and the coping skills and techniques used to counter the potentially detrimental effects of perfectionism. The findings highlighted the multidimensional nature of perfectionism and the need for future research to further explore the efficacy of techniques athletes use to promote healthy and reduce unhealthy facets of perfectionism.